A Robust Hybrid Algorithm for Image Steganography - Soi, Divya; Bhupinder, Bhupinder (International Journal of Computer Sciences and Engineering, 2020)
Image Steganography is the mechanism of hiding the critical information on the segment of the image that can either be least significant or most significant in nature. Image Steganography involves multiple images that are merged together to achieve a common image that is transferred over a digital medium. Proposed system uses slant let transformation to achieve better result of image security in terms of accuracy. Accuracy is achieved by minimising mean square error and improving peak signal to noise ratio.